A comparative study on nitridation mechanism and microstructural development of porous reaction bonded silicon nitride in the presence of CaO, MgO and Al2O3. Issue 3 (2nd July 2020) - Nikonam-Mofrad, Raheleh; Pugh, Martin D.; Drew, Robin A. L.
ABSTRACT: During the in-situ nitridation of Si in the presence of CaO, MgO and Al2 O3 formation of reaction bonded silicon nitride ceramics (RBSN) having various microstructures indicated the possibility of different nitridation mechanisms operating. Experimental evidence suggested that, whereas the morphology of pores was controlled by nitridation of Si(g) in CaO-RBSN and SiO(g) in Al2 O3 -RBSN, a combination of these two reactions occurred during the nitridation of the MgO-RBSN. By inhibiting the growth of whiskers and maximizing the α/β ratio, the CaO addition led to the formation of matte grains creating clean spherical cavities with d < 40 µm and flexural strength of 0.8 MPa. In contrast, when using Al2 O3 additions, a microstructure with a very low α/β ratio, fine inter-particle pores and 2.4 MPa flexural strength, reinforced with interlocking whiskers, was produced. The highest porosity (85%) and the lowest strength (0.3 MPa) occurred in the MgO-RBSN, which was composed of both matte grains and fine whiskers. Local supersaturation and low content of β-nuclei led to the formation of anisotropic β-grains with a bimodal microstructure in heat-treated CaO-RBSN while a unimodal microstructure was observed in heat-treated MgO-RBSN. No porosity loss or β-grain growth occurred in the heat-treated Al2 O3 -RBSN.